Effects of wound infection on prognosis after laparoscopic abdominoperineal resection of rectal cancer - Huang, Wang; Wei, Zheng-qiang; Qiu, Yu-hao; Tang, Gang; Sun, Hao (Frontiers in Oncology, 2023)
Background In two facilities in Chongqing, this research sought to retrospectively evaluate the effects of perineal wound infection on survival after laparoscopic abdominoperineal resection (LAPR) of rectal cancer. Methods To obtain clinical information on patients who underwent LAPR between January 2013 and December 2021, we performed a multicenter cohort study. A total of 473 patients were enrolled: 314 in the non-infection group and 159 in the group with perineal infection. The general data, perioperative conditions, and tumor outcomes between groups were analyzed. The infection rates, recurrence rates, and survival rates of the two centers were compared. Results The age, height, weight, body mass index (BMI), preoperative complications, preoperative treatment, and intraoperative conditions of patients in the LAPR infection group were not statistically different from those in the non-infection group. The percentage of men, typical postoperative hospital stay, length of initial postoperative therapy, and recurrence and metastasis rates were all considerably higher in the infection group than those in the non-infection group. Wound infection was an independent factor affecting tumor recurrence and metastasis after LAPR as well as an independent factor shortening patient survival time according to multivariate analysis. The incidence of wound infection, the rate of recurrence, and the rate of mortality did not vary significantly across sites. Conclusion Wound infection after LAPR increases the mean postoperative hospital stay, prolongs the time to first postoperative treatment, and decreases the disease-free survival (DFS) and overall survival (OS). Therefore, decreasing the rate of LAPR wound infection is expected to shorten the postoperative hospital stay and prolong the patient DFS and OS. Patients with postoperative infection may require intensive adjuvant therapy.